2012
DOI: 10.4049/jimmunol.1100887
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Dendritic Epidermal γδ T Cell Ligands Are Rapidly and Locally Expressed by Keratinocytes following Cutaneous Wounding

Abstract: TCR specific activation is pivotal to dendritic epidermal T cell (DETC) function during cutaneous wound repair. However, DETC TCR ligands are uncharacterized and little is known about their expression patterns and kinetics. Using soluble DETC TCR tetramers, we demonstrate that DETC TCR ligands are not constitutively expressed in healthy tissue, but are rapidly upregulated following wounding on keratinocytes bordering wound edges. Ligand expression is tightly regulated with down-modulation following DETC activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 25 publications
3
81
0
Order By: Relevance
“…The TRGV5 gene rearrangement detected in our study corresponds to that reported for the previously described invariant Vγ5 + dendritic epidermal T cells (DETCs) (43,44). DETCs are the most common skin-resident γδ T cell population and have been reported to recognize a stress-induced self-antigen derived from keratinocytes (46,47). In contrast, the TRGV6 gene rearrangement described herein corresponds to that reported for canonical γδ T cells residing in the liver, placenta, kidney, uterus, tongue and other mucosal sites (33,45).…”
Section: Trgj1*01supporting
confidence: 57%
See 1 more Smart Citation
“…The TRGV5 gene rearrangement detected in our study corresponds to that reported for the previously described invariant Vγ5 + dendritic epidermal T cells (DETCs) (43,44). DETCs are the most common skin-resident γδ T cell population and have been reported to recognize a stress-induced self-antigen derived from keratinocytes (46,47). In contrast, the TRGV6 gene rearrangement described herein corresponds to that reported for canonical γδ T cells residing in the liver, placenta, kidney, uterus, tongue and other mucosal sites (33,45).…”
Section: Trgj1*01supporting
confidence: 57%
“…Multiple gene rearrangements encoding for the same CDR3 aa sequence, as reported here, favor antigen specificity as the driving force behind the observed pathogen-induced T cell expansion. Although it is unclear whether the γδ T cell TCR reactivity was against a yet-tobe-described S. aureus-derived antigen or self-antigen as previously postulated (46,47), it is clear that this distinctive TRGV5/ V6-encoded CDR3 aa sequence is critical for mediating robust immune protection against pathogens at the skin and potentially other barrier sites. Furthermore, the TRGV5 and TRGV6 CDR3-encoding sequences correlated with TBX21 expression, providing an explanation for increased γδ T cell production of TNF/IFN-γ.…”
Section: Trgj1*01mentioning
confidence: 99%
“…DETC play an essential role in wound repair (21), and therefore, we sought to determine whether DETC are the source of IL-17A in the epidermal compartment. We reasoned that direct TCR ligation would be critical for IL-17A production by DETC, because DETC become activated through their TCR by recognition of self antigens expressed on wounded keratinocytes (25,42). Indeed, we observed that freshly isolated and sorted Vγ3 + DETC stimulated with anti-CD3ε strongly induced IL-17A mRNA and protein ( Figure 2, A and B).…”
Section: Introductionmentioning
confidence: 85%
“…Tightly interspersed with the epidermal LC network in mice is a similarly dense network of DETCs (13). These T cells are important for efficient wound repair and respond to signals from stimulated keratinocytes (14,15). Similarly, populations of epidermal T cells are also present in humans and may also contribute to wound repair (16).…”
Section: Resultsmentioning
confidence: 99%